Directions of development of palliative care based on the literature - Zasowska-Nowak, Anna (Medycyna Paliatywna/Palliative Medicine, 2022)
The growing demand for palliative care and the levelling of differences in access to this form of care constitute very important challenges for the modern world. Despite significant progress in recent years in accessing palliative care and recognizing the human entitlement to alleviate suffering as one of its fundamental rights, access to opioid medications and pain management remain insufficient in many geographic regions. In the near future, palliative care must be prepared for the next challenges that await it, related to the increase in the number of patients and the need to provide them with personalized care, adapted not only to the stage of the disease and reported somatic symptoms, but also dependent on social, cultural, and religious conditions. To achieve the above goals, it is necessary to improve access to education, as well as appropriate economic growth of individual countries, allowing for the optimal use of existing human resources and infrastructure. Improving the quality of palliative care for cancer patients through its integration with oncological care is undoubtedly another action aimed at the needs of this group of patients to improve their quality of life. It is also particularly important to change the definition of palliative care and adapt it to the changing needs of the modern world.